(untitled) (Huellas, 2016)
The urban growth ofBahía Blancacity has intervened the northern periurban area with the consequent modification of the natural landscape, in particular the drainage network. Geo-morphological maps are instruments that make possible a temporal analysis and facilitate the visualization of processes and forms of the surface. The GIS software facilitates the analysis of the changes produced in the natural environment due to urban development. The aim of this work is to study the mutual implications between the geo-morphological dynamics and the urbanization process in the northern periurban area ofBahía Blancacity. The identification of geoforms and processes was carried out on the basis of geological documents of the area, visual analysis of high resolution satellite images (2009 and 2015) and field control. A geographic database was implemented using ArcGIS 10® that enables temporal analysis and the development of thematic cartography. Natural areas modified by urbanization and new periurban areas affected by hydro-geo-morphological dynamics were identified from a quantitative and qualitative cartographic analysis.